Safety and efficacy comparison of single-stage and two-stage ERCP combined with laparoscopic cholecystectomy: a meta-analysis and systematic review - Tai, Jian-Xiong; Zhang, Qingxiang (Frontiers in Medicine, 2025)
ObjectiveThis meta-analysis aims to assess the safety and efficacy of single-stage and two-stage ERCP combined with laparoscopic cholecystectomy in the management of bile duct stones.MethodsA comprehensive search was conducted in PubMed, Embase, Cochrane Library, and Web of Science databases to identify prospective randomized controlled studies comparing the effectiveness of single-stage ERCP combined with laparoscopy, also known as Laparoscopic-Endoscopic Rendezvous (LERV), and the sequential two-step approach of ERCP followed by laparoscopic cholecystectomy (ERCP+LC). Stone clearance success rate, incidence of complications, occurrence of pancreatitis, and hyperamylasemia were analyzed using Stata software.ResultsNine studies involving a total of 1,003 participants were included in the analysis, with 505 patients undergoing sequential surgery and 498 patients receiving LERV treatment. The LERV group exhibited a significantly higher stone clearance rate compared to the sequential surgery group (RR = 0.62, 95% CI: 0.49–0.79). The incidence of pancreatitis was significantly higher in the sequential surgery group compared to LERV (RR = 1.90, 95% CI: 1.61–2.24). Similarly, the occurrence of hyperamylasemia was significantly higher in the sequential surgery group compared to LERV (RR = 1.93, 95% CI: 1.55–2.40).ConclusionThe findings of this meta-analysis support the effectiveness of LERV as a treatment option for bile duct stones. LERV demonstrates superior outcomes compared to the sequential two-step approach of ERCP followed by laparoscopic cholecystectomy (ERCP+LC). Specifically, LERV shows improved stone clearance success rates and a decreased incidence of pancreatitis. These results suggest that LERV is a safe and efficient procedure for the management of bile duct stones.Systematic review registration2025100075, https://doi.org/10.37766/inplasy2025.10.0075.